PENGARUH PERSEPSI TENTANG KANKER PAYUDARA TERHADAP PERILAKU DETEKSI DINI KANKER PAYUDARA PADA WANITA USIA SUBUR DI WILAYAH PUSKESMAS SALAM KABUPATEN MAGELANG - Arfiana, Arfiana (JURNAL KEBIDANAN, 2015)
Breast cancer is a terrified cancer and always happened to most women. Most breast cancer cases can not be cured, because of in advanced stadium.In Magelang district 2011, there were breast cancers in Magelang District Hospital about 312 outpatient cases, In 2012, there were 192 outpatient cases. In January â Maret 2013, there were 38 outpatient. Less in early detection awareness can cause cancer in advanced stadium it can not be cured. This research is to know the effect of perception about breast cancer among women at reproductive age toward early detection attitude of breast cancer. The research is an explanatory research with cross sectional approach. Population that was used in this research May 2014 was fertile women 15 â 49 years old in Salam Public Health Care, Magelang District while the samples were gotten by using solvin pattern was 373 women at reproductive age, and getting the samples in each strata by using random sampling. The result of the research showed that there are 76,7% women at reproductive age have bad attitude, variabel that give significant effect to early detection for breast cancer is benefit perception (p value : 0,000), with OR/Exp(B): 0,241, benefit perception is the protective factor for women at reproductive age to have early detection for breast cancer. Women at reproductive age is hoped to increase the effort of early detection for breast cancer in giving breast examination by medical profession (CBE) or check to the hospital to do mammograph test, and for midwife as medical staff is hoped to increase the knowledge of women at reproductive age about early detection for breast cancer by pressing health education about CBE and mammograph and also for health department to develop health promotion about early detection for breast cancer in CBE and mammograph.